MicroRNA-mediated regulation of key signaling pathways in hepatocellular carcinoma: A mechanistic insight - Ruiz-Manriquez, Luis M.; Carrasco-Morales, Oscar; Sanchez Z, E. Adrian; Osorio-Perez, Sofía Madeline; Estrada-Meza, Carolina; Pathak, Surajit; Banerjee, Antara; Bandyopadhyay, Anindya; Duttaroy, Asim K.; Paul, Sujay (Frontiers in Genetics, 2022)
Hepatocellular carcinoma (HCC) is the most common type of primary liver cancer. The molecular pathogenesis of HCC varies due to the different etiologies and genotoxic insults. The development of HCC is characterized by complex interactions between several etiological factors that result in genetic and epigenetic changes in proto-onco and/or tumor suppressor genes. MicroRNAs (miRNAs) are short non-coding RNAs that also can act as oncomiRs or tumor suppressors regulating the expression of cancer-associated genes post-transcriptionally. Studies revealed that several microRNAs are directly or indirectly involved in cellular signaling, and dysregulation of those miRNAs in the body fluids or tissues potentially affects key signaling pathways resulting in carcinogenesis. Therefore, in this mini-review, we discussed recent progress in microRNA-mediated regulation of crucial signaling networks during HCC development, concentrating on the most relevant ones such as PI3K/Akt/mTOR, Hippo-YAP/TAZ, and Wnt/β-catenin, which might open new avenues in HCC management.